2011
DOI: 10.4049/jimmunol.1003986
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Is Critical for Induction of Arthritis, Osteoclast Formation, and Maintenance of Bone Mass

Abstract: The role of IL-23 in the development of arthritis and bone metabolism was studied using systemic IL-23 exposure in adult mice via hydrodynamic delivery of IL-23 minicircle DNA in vivo and in mice genetically deficient in IL-23. Systemic IL-23 exposure induced chronic arthritis, severe bone loss, and myelopoiesis in the bone marrow and spleen, which resulted in increased osteoclast differentiation and systemic bone loss. The effect of IL-23 was partly dependent on CD4+ T cells, IL-17A, and TNF, but could not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 34 publications
11
133
0
1
Order By: Relevance
“…In the latter model IL-23 was necessary for induction of lung fibrosis by transforming growth factor ␤. There is evidence that IL-23 might have a different effect under inflammatory conditions versus noninflammatory conditions: it can mediate bonedestructive processes (32,33) and is found within inflammatory lesions in the gut mucosa of patients with Crohn's disease (34), but also induces increased bone mass under noninflammatory conditions (35). We and others have hypothesized that new bone formation starts from fibrous tissue and that the development of fibrous tissue is crucial in AS (4,13,14).…”
Section: Il-23 In the Spine Of Patients With Asmentioning
confidence: 99%
“…In the latter model IL-23 was necessary for induction of lung fibrosis by transforming growth factor ␤. There is evidence that IL-23 might have a different effect under inflammatory conditions versus noninflammatory conditions: it can mediate bonedestructive processes (32,33) and is found within inflammatory lesions in the gut mucosa of patients with Crohn's disease (34), but also induces increased bone mass under noninflammatory conditions (35). We and others have hypothesized that new bone formation starts from fibrous tissue and that the development of fibrous tissue is crucial in AS (4,13,14).…”
Section: Il-23 In the Spine Of Patients With Asmentioning
confidence: 99%
“…The use of minicircle DNA technology to express IL-23 in the hepatocytes of B10.RIII mice resulted in a destructive polyarthritis that was found to be independent of CD4ϩ T cells (15). Recently, Sherlock et al (16) reported that the resulting in vivo expression of IL-23 was sufficient to induce enthesitis and entheseal new bone formation in the initial complete absence of synovitis.…”
mentioning
confidence: 99%
“…However, in contrast to IL-17-deficient mice, IL-23 knockout mice are completely protected from bone and joint destruction in the collagen-induced arthritis model, indicating that the IL-23-induced bone loss may not be entirely mediated by IL-17, and raising the question whether IL-23 can directly stimulate OCs. Recent work supports this hypothesis suggesting that IL-23 promotes OCs formation (Adamopoulos et al, 2011;Chen et al, 2008;Hu et al, 2013;Yago et al, 2007). Other recent in vivo studies suggest that IL-23 inhibits OC formation via T cells (Quinn et al, 2008).…”
Section: Estrogen Deficiency and Cytokinesmentioning
confidence: 73%